Sistim Informasi Operasi Jaringan Irigasi untuk Modernisasi Pengelolaan Irigasi serta Peningkatan Proses Dialogis Petani dengan Pemerintah - Wisnu Wardana; Sigit Supadmo Arief; Darmadi Darmadi; Anjar Suprapto (agriTECH, 2003)
Managing irrigation water is not only distribute irrigation water .to the assigned field, but it is also include arranging the cropping pattern and scheduling in order to fit it to the availability of irrigation water. Cropping pattern and scheduling plan is the important things because each crop has its characteristics in water consumptions and on the other hand there is a limited water resources. There are three important factors in determining of cropping pattern and scheduling: (i) farmers need, (ii) service target and (iii) the ability of irrigation scheme. in the era of Government Regulation No 77/01, farmers participation in operation and maintenance (O&M) of irrigation scheme is an important things. The consequences is the managers of irrigation scheme have to negotiate these cropping pattern and scheduling plan as well as its water allocation to the farmers. The aim of this study is to prepare the tool to make easier during negotiation for determining the cropping pattern and scheduling. This tool is a computer program of information systems used for O&M of an irrigation scheme, and it is based on the availability of irrigation water, irrigation scheme performance, crop characteristics as well as its water consumption, market driven as well as the income offarmers.